Bentuk Pola Spasial Permukiman di Kecamatan Salahutu - Rumalarua, Gresye; Titaley, Stevianus; Botanri, Adnan Affan Akbar (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Salahutu District is directly adjacent to Ambon City so that it has experienced rapid development due to the expansion of urban activities and is supported by various potentials such as ports, fisheries, trade and services and other potentials. This attracts residents to settle and can indirectly affect the distribution of settlements by forming certain patterns both clustered, random, and uniform. This study aims to identify spatial patterns of settlement distribution in Salahutu District. This study uses a quantitative approach with Nearest Neighbour Analysis analysis which aims to identify spatial patterns. The results showed that Salahutu District had most settlement distribution patterns grouping as many as 47 zones or 94% and the rest formed random patterns as many as 3 zones or 6%. The characteristics of residential zones with a clustering pattern have relatively close distances between settlements and high building density. While the characteristics of residential zones with random patterns have relatively long distances between settlements and lower building density. The existence of family ties that are still closely established causes settlements to form in groups so that it affects the maintenance of local identity of the community that is still maintained. The importance of the results of this study is to anticipate the development of settlements that are not well planned so that it can cause the addition of slums as bad areas in Salahutu District